EXPERIMENTAL INVESTIGATION THE WEAR OF BANDAGES LOCOMOTIVES ВЛ11 M WITH DIFFERENT PROFILES - Korotenko, M. L.; Zabolotnyi, O. M.; Neduzha, L. O.; Nesterenko, M. M.; Yahoda, D. O. (Science and Transport Progress, 2005)
The experimental research of the bandage wear has fun conducted concerning electric locomotive performance under the mountain conditions of the Lvov railway. The operation periods of an electric locomotive have been considered as for the various wheel profile structures.